2015
DOI: 10.1016/j.jphs.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Different chronotherapeutic effects of valsartan and olmesartan in non-dipper hypertensive patients during valsartan treatment at morning

Abstract: This study was undertaken to evaluate the differences in chronotherapeutic effects of angiotensin-II receptor blockers, valsartan and olmesartan in hypertensive patients with non-dipper blood pressure (BP) pattern during valsartan at morning. Ninety four patients were enrolled, and 40 patients were judged to be non-dippers. In these patients, same dose of valsartan was changed to evening (Val-E, n = 12), or olmesartan (equivalent dose of valsartan) was given at morning (Olm-M, n = 13) or evening (Olm-E, n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Calcium antagonists, particularly amlodipine, increase nocturnal urine volume by selectively dilating renal afferent arterioles. Olmesartan normalizes non‐dipping blood pressure . It was reported that taking an α1 receptor blocker at night significantly decreased nocturnal blood pressure in non‐dippers and risers .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium antagonists, particularly amlodipine, increase nocturnal urine volume by selectively dilating renal afferent arterioles. Olmesartan normalizes non‐dipping blood pressure . It was reported that taking an α1 receptor blocker at night significantly decreased nocturnal blood pressure in non‐dippers and risers .…”
Section: Discussionmentioning
confidence: 99%
“…The group has presented similar findings related to olmesartan (ARB) which has a terminal half-life of ~13-h (52, 100). In contrast, Ushijima et al (101), report no additional benefit of taking olmesartan in the evening compared to the morning. Moreover, the study confirms decreased BP during sleep when valsartan (ARB with terminal half-life of 6–9 hours) is taken at bedtime compared to the morning (100, 101).…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, Ushijima et al (101), report no additional benefit of taking olmesartan in the evening compared to the morning. Moreover, the study confirms decreased BP during sleep when valsartan (ARB with terminal half-life of 6–9 hours) is taken at bedtime compared to the morning (100, 101). Thus, it is surprising that Zappe et al conclude that once daily administration of valsartan resulted in similar 24-h BP control regardless of dosing time and when compared to administration of a long-acting ACEI taken in the morning (102).…”
Section: Resultsmentioning
confidence: 95%
“…20 Finally, reducing morning BP surge <45 mmHg, the third step for the perfect BP control, is important for the prevention of cardiovascular events. 21 Recently, a study comparing the effect of valsartan and olmesartan in non-dipper hypertensive patients, 22 showed that evening administration of valsartan and olmesartan was effective for recovering dipping pattern, but the study was focused on the chronotherapeutic effects of valsartan and olmesartan and their comparative efficacy. There is still little data on comparative efficacy of night-time ABP-lowering effect among ARBs.…”
Section: Discussionmentioning
confidence: 99%